The determinants of malnutrition in children below five years at Seshego District Hospital, Capricorn District, Limpopo Province, South Africa. - Mmako, Lettie Ndweleng. (My University, 2023)
Background Malnutrition is one of the big problems of public health in developing countries. It is still a persistent public health issue particularly among the poorest and vulnerable groups. Malnutrition of children below the age of 5 put more burden on health systems of most countries. It accounts for high morbidity and mortality in children below the age of five years. The nutritional status of children below five years can also be used to measure the outcome for children’s health. It is therefore important to provide good nutrition to children as an important factor of general well-being. Methods The study was quantitative and retrospective in nature. The prevalence of malnutrition and the factors that contribute to malnutrition was quantified. The researcher has no control over the exposure. Population was the existing records of children below five years admitted at Seshego district hospital with malnutrition between January 2017 and December 2021. The study was probable, simple random sampling method was used whereby files was selected randomly from the patient filing register. The data collecting tool was developed and it was divided into three sections: the immediate factor questions, intermediate factor questions and distal factor questions. Descriptive statistical analysis was undertaken using the STATA statistical software version 6A for Windows (STATA Corporation, College Station, Texas) in order to identify frequencies and percentages of answers to the research questions. The statistical significance of the relationships between the selected variables was determined using the t-test. The level of significance was set at 0.05. Findings The results showed that most of the children were in the age group 1year-1year 11 months at 46.5%. The prevalence showed that SAM was high at 59.5% and MAM was low at 40,9%. The prevalence of MAM and SAM stratified by the age of the child showed that children below 1 year, 41.9% of them have MAM and 41,1% have SAM. The severity of malnutrition decreased with the increase of the age of the child. The current study showed that statistically there is no significance among the variables in terms of the determinants. The P-values are above 0.05. vi Conclusion The study had showed high rate of MAM and SAM. This will urge the public health sector to put the interventions in place to prevent malnutrition from primary stage. In the future a further study with primary data should be done to examine the determinants of malnutrition among children below 5 years.
(M.P.H. (Health Sciences)) -- University of Limpopo, 2023.
Keywords: Malnutrition; Prevalence; Determinants; Children; Food preferences.; Nutrition.; Malnutrition in children.